A systematic review of the impact of center volume in dialysis. (December 2015) - Pieper, Dawid; Mathes, Tim; Marshall, Mark
Abstract Background A significant relationship exists between the volume of surgical procedures that a given center performs and subsequent outcomes. It seems plausible that such a volume–outcome relationship is also present in dialysis. Methods MEDLINE and EMBASE were searched in November 2014 for non-experimental studies evaluating the association between center volume and patient outcomes [mortality, morbidity, peritonitis, switch to hemodialysis (HD) or any other treatment], without language restrictions or other limits. Selection of relevant studies, data extraction and critical appraisal were performed by two independent reviewers. We did not perform meta-analysis due to clinical and methodological heterogeneity (e.g. different volume categories). Results 16 studies met out inclusion criteria. Most studies were performed in the US. The study quality ranged from fair to good. Only few items were judged to have a high risk of bias, while many items were judged to have an unclear risk of bias due to insufficient reporting. All 10 studies that analyzed peritoneal dialysis (PD) technique survival by modeling switch to HD or any other treatment as an outcome showed a statistical significant effect. The relative effect measures ranged from 0.25 to 0.94 (median 0.73) in favor of high volume centers. All nine studies indicated a lower mortality for PD in high volume centers, but only study was statistical significant. Conclusions This systematic review supports a volume–outcome relationship in peritoneal dialysis with respect to switch to HD or any other treatment. An effect on mortality is probably present in HD. Further research is needed to identify and understand the associations of center volume that are causally related to patient benefit.